CO2 capture in a chemical looping combustion power plant evaluated with an advanced exergetic analysis. Issue 3 (10th September 2013) - Petrakopoulou, Fontina; Tsatsaronis, George; Morosuk, Tatiana
<x xml:space="preserve">Abstract</x> CO2 capture and storage (CCS) is a way to minimize harmful emissions generated from the combustion of fossil fuels in power plants. Measures to increase the thermodynamic efficiency of power plants incorporating CCS can improve their economic viability, as well as reduce the environmental impact of such applications. Exergy‐based analyses are tools that aid the evaluation of energy conversion systems and reveal paths to improve them. In this article, an advanced exergetic analysis is applied to a near‐zero‐emission power plant that incorporates chemical looping combustion. The final goal is to reveal ways toward a more efficient and less polluting operation of the power plant. The objectives of the article further include the quantification of the different parts of the exergy destruction and the demonstration of the advantages of using such an advanced method. It has been found that most of the exergy destruction of the plant is endogenous and, for the majority of the components, unavoidable. When calculating the total avoidable exergy destruction caused by each component, it is found that the most important plant component is the reactor unit, followed by the expander and the compressor of the gas turbine. Lastly, the potential for improvement is found to lie mainly with the internal operation of the components, while the interactions among the plant components are less significant. © 2013 American Institute of Chemical Engineers Environ Prog, 33: 1017–1025, 2014